NegevPulse: Crowdsourced Digital Mapping for Visibility in Unrecognized Bedouin Villages - Chassidim, Hadas; Shnaiwer, Tasneem; Algergawi, Israa; Abu Samor, Somaya; Yossef Ravid, Batel (Street Art & Urban Creativity, 2025)
Urban Digital Twin (UDT) systems are increasingly central to data-driven urban governance, yet their effectiveness relies on comprehensive datasets. In informal settlements, where official data are missing, UDTs struggle to function. This paper introduces NegevPulse, a participatory digital mapping system designed for unrecognized Bedouin villages in the Negev, Israel. By integrating community knowledge through a trust-based crowdsourcing mechanism, the platform generates reliable spatial data to support navigation and emergency access. The study highlights how participatory mapping can address data poverty and extend the applicability of UDTs to undocumented spaces, promoting visibility and spatial justice.